Application of nitrogen and 2,4-D as growth regulator in corn II. Nutrient contents in leaves and grains - Silva, Paulo Regis Ferreira da; Okuyama, Lauro Akio (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out at the Estação Experimental Agronômica/Universidade Federal do Rio Grande do Sul, in Guaíba, RS, Brazil, to evaluate the effects of nitrogen and 2,4-D applications on nutrient contents of corn by two nitrogen levels (40 and 120 kg/ha N) and four 2,4-D levels (0, 80, 160 and 240 g e.a./ha). Nitrogen, phosphorus, potassium, calcium, and magnesium contents in leaves were determined eleven days after 2,4-D appplication and, at twelve day intervals, from silking to 60 days after silking. 2,4-D treatment affected significantly only potassium content in leaves, sampled eleven days after its application. With 120 kg/ha N, nitrogen and phosphorus contents in leaves were higher than with 40 kg/ha N, from silking to 60 days after silking. The highest dosis of N per ha increased the N content in the leaves. In addition, it increased the P content in the leaves, from silking to 60 days after silking. Nutrient contents in grains were not affected by 2,4-D and nitrogen treatments.